2014
DOI: 10.1177/1533317514534953
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Against Gangliosides in Patients With Dementia

Abstract: This study indicates that elevated IgM anti-GM1 may be connected with the neurodegeneration in older patients with severe dementia and that AD may also be associated with increased IgM anti-GD1b levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
(81 reference statements)
1
15
0
Order By: Relevance
“…In SS, antiganglioside antibodies were associated with evidence of neuropathy . Furthermore, antiganglioside antibodies may be related to dementia . In our study, patients with PSS had significantly higher rate of seropositivity for antiganglioside antibodies compared to controls.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In SS, antiganglioside antibodies were associated with evidence of neuropathy . Furthermore, antiganglioside antibodies may be related to dementia . In our study, patients with PSS had significantly higher rate of seropositivity for antiganglioside antibodies compared to controls.…”
Section: Discussionsupporting
confidence: 45%
“…Anti‐phospholipid antibodies, anti‐N‐methyl‐D‐aspartate (NMDA) receptor and anti‐ribosomal‐p autobodies in SLE and anti‐thyroid antibodies in Hashimoto's ensephalopathy have been reported . Moreover, antiganglioside antibodies may have a potential role in neurological manifestations of several diseases, such as neurodegenerative diseases, dementia, SLE, SS, mixed cryoglobulinemia and idiopathic systemic vasculitis . Likewise, antiganglioside antibodies are related to cognitive dysfunction in pediatric neuropsychiatric SLE .…”
Section: Introductionmentioning
confidence: 99%
“…Gangliosides' binding induces Aβ peptide oligomerization. GM1 and GT1b have four sugar moieties in common, however, GT1b has three sialic molecules more compared to asialo-GM1 that doesn't contain sialic rests [60].…”
Section: Discussionmentioning
confidence: 99%
“…In more recent reports Mandal et al demonstrated with NMR studies, the interaction of membrane-bound α-synuclein with Aβ. The presence of multiple sites of interaction between α-synuclein and Aβ might be important in determining the overlapping patho-cascades of AD and PD seen in DLB [60]. Preventing the interaction of membrane-bound α-synuclein with Aβ peptide would be an important therapeutic research target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation